Spatial Analysis of Leptospirosis Disease in Bantul Regency Yogyakarta - Sulistyawati, Sulistyawati; Nirmalawati, Trias; Mardenta, Ricadone Nita (Jurnal Kesehatan Masyarakat, 2016)
Leptospirosis has still become a public health problem in the world, especially in developing countries which have tropical and subtropical climate such as in Indonesia. This research aims at investigating the spread and analyzing the cluster of Leptospirosis cases by using GIS. This research was conducted in 2015 using descriptive qualitative method. The total cases were 35 cased during May-Dec 2014 in Bantul Regency, Yogyakarta. The data consisted of secondary and primary data collected by using GPS. Univariate and spatial analysis were performed through SaTScan, QGIS desktop 2.4.0 and ArcGIS 1.1.0. The result shows that the distribution of Leptospirosis case in Bantul Regency is equally distributed in all districts with plain topography. The highest case occurs in May (12 cases). Clustering pattern is significant with p value= 0,001 with 11 cases in the cluster.